Synthesis and catalytic performance of ferrocene‐based compounds as burning rate catalysts. (27th March 2017) - Zain‐ul‐Abdin; Wang, Li; Yu, Haojie; Saleem, Muhammad; Akram, Muhammad; Khalid, Hamad; Abbasi, Nasir M.; Khan, Rizwan Ullah
Abstract : To overcome migration problems of ferrocene‐based burning rate catalysts and to enhance burning rate of ammonium perchlorate (AP)‐based propellants, eleven ferrocene‐based compounds (1 –11 ) were synthesized by the condensation reaction of ferrocenecarbonyl chloride with corresponding amines and alcohols. The synthesis of 1 –11 was confirmed using 1 H NMR, Fourier transform infrared and UV–visible spectroscopy. Their electrochemical properties were analyzed using cyclic voltammetry. The compounds showed redox behavior due to the presence of ferrocene. Their catalytic behavior in the thermal decomposition of AP was investigated using thermogravimetry (TG) and differential TG (DTG). In the presence of 5 wt% 1 –11, the thermal decomposition temperature of AP was significantly decreased. TG and DTG analyses showed that 1 –11 had a good catalytic effect in the thermal decomposition of AP. Anti‐migration studies showed that migration of 1 –11 was slower than that of 2, 2‐bis(ethylferrocenyl)propane (catocene) and ferrocene. The effect of the presence of polar elements like oxygen and nitrogen on anti‐migration behavior of small ferrocene‐based compounds was also investigated. Oxygen‐containing compounds showed better anti‐migration behavior than nitrogen‐containing compounds. Abstract : Eleven ferrocene‐based compounds were successfully synthesized. Electrochemical and anti‐migration properties of the synthesized compounds were analyzed. Burning rate catalytic performance of the synthesized compounds was also investigated on the thermal decomposition of AP.